Edukasi Kesehatan Jiwa Bagi Orang dengan HIV AIDS dalam Menghadapi Covid-19 - Selvi Alfrida Mangundap; Rina Tampake; Dafrosia Darmi Manggasa (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
The Covid-19 pandemic has caused mental health problems in the community, including at risk groups, namely people with HIV AIDS due to fear of infection due to decreased immunity. Mental health and psychosocial problems must be addressed immediately so as not to cause physical health problems and other problems such as economic, social and cultural. The purpose of the activity is to increase the knowledge, attitudes and abilities of participants in overcoming mental health and psychosocial problems. The activity was carried out in Palu City with educational methods in the form of socialization and training. Participants are people with HIV AIDS, totaling 76 people. The results of the activity are participants with good knowledge as much as 44.7% increased to 84.2% and positive attitude as much as 52.6% increased to 88.2%. Suggestions for health workers to routinely make efforts to improve mental and psychosocial health for people with HIV AIDS by making efforts to overcome anxiety by doing progressive muscle relaxation and efforts to create relaxed physical, positive emotions, positive thoughts, positive behavior, positive relationship and spiritual positive. ABSTRAK Pandemi Covid-19 menimbulkan masalah kesehatan jiwa pada masyarakat termasuk pada kelompok beresiko yaitu orang dengan HIV AIDS akibat takut tertular karena imunitas yang menurun. Masalah kesehatan jiwa dan psikososial harus segera ditangani agar tidak menimbulkan permasalahn kesehatan fisik serta masalah lain seperti ekonomi, sosial dan budaya. Tujuan kegiatan untuk meningkatkan pengetahuan, sikap dan kemampuan peserta dalam mengatasi masalah kesehatan jiwa dan psikososial. Kegiatan dilaksanakan di Kota Palu dengan metode edukasi berupa sosialisasi dan latihan. Peserta adalah orang dengan HIV AIDS yang berjumlah 76 orang Hasil kegiatan yaitu peserta dengan pengetahuan baik sebanyak 44,7% meningkat menjadi 84,2% dan sikap positif sebanyak 52,6% meningkat menjadi 88,2%. Saran bagi petugas kesehatan agar rutin untuk melakukan upaya peningkatan kesehatan jiwa dan psikososial bagi orang dengan HIV AIDS dengan melakukan upaya untuk mengatasi kecemasan dengan melakukan relaksasi otot progresif serta upaya untuk menciptakan fisik rileks, emosi positif, pikiran positif, perilaku positif, relasi positif dan spiritual positif.